Pengaruh Dosis Serum Lateks terhadap Koagulasi Lateks (Hevea brasiliensis) - Maryanti, Maryanti; Edison, Rachmad (Jurnal Agro Industri Perkebunan, 2016)
Waste water that comes out of the milling process latex factory so many and has not been utilized, often becomes a problem for the environment if the handling is not optimal. This wastewater is known as latex serum. Latex serum can be used as an alternative coagulant because it has a low pH and containing metal ions. Low pH will lower the pH of the latex to the isoelectric point and cations of alkali metals will reduce electro kinetic potential latex, so latex becomes frozen. Research purposes to determine the length of time coagulation of latex, yield of coagulum and yield dry rubber. Research conducted at the Laboratory of Plant Production at Politeknik Negeri Lampung. The material used are latex serum and latex and other materials. The equipment used is the coagulation bath, digital pH meter, a wooden spatula, milling, stopwatch, and other analysis tools. The research tested in completely randomized design with one independent variable used is composed of coagulant doses: 0%, 4%, 8%, 12%, 16% and 20% v/v and replicated 3 times. The observation are pH of latex serum, pH oflatex, coagulation time, and yield dry rubber. The result showed that for pH of latex serum is 4.9, pH of latex is 6.22, the best doses to coagulation is 20% with time to coagulation 17 minute time, coagulum yield of 59.83 and dry rubber yield of 42.10.Keywords: coagulant, latex coagulation, latex serumPermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/36